Development of Short Carbon Fibre Reinforced Polypropylene Composite for Car Bonnet - Rezaei, Fateme (2006)
Carbon fiber reinforced thermoplastics are increasingly used for high performance composites, particularly for the automotive industry. This study focuses on the development of short carbon fiber reinforced polypropylene (SCF/PP) for use as car bonnet in replacement for steel. The scope of work includes formulation of the composites, evaluation of mechanical, thermal and morphological properties as well as comparative performance to that of steel. The composites were prepared by melt blending using chopped fibers of 5 sizes;0.5 mm, 1 mm, 2 mm, 5 mm and 10 mm respectively for fiber loading of 1, 2, 3, 4, 5, 6 and 7% weight fraction. Sheets of 1 mm and 3 mm thickness were compression moulded to be used for further testing. The sheets were tested for mechanical properties such as density (ASTM D792), tensile strength (ASTM D638), flexural strength (ASTM D790), Rockwell hardness (ASTM D785) and Izod impact values (ASTM D256). The effects of fiber length on thermal properties of the composites were evaluated using thermogravimetric (TGA) and dynamic mechanical analysis (DMA). TGA was used to evaluate composite decomposition and stability whilst DMA was utilized to evaluate parameters such as the glass transition temperature, Tg, storage modulus, E’, loss modulus, E” and tan δ. The morphology of failure was observed using scanning electron microscopy (SEM). The performance of the composites was compared to the current material in use (mild steel) for mechanical and thermal properties. The mechanical properties of the composites were enhanced with increase in weight fraction as well as fiber size. The SEM micrograph of fractured surfaces showed that there was good fiber-matrix adhesion for composites with longer fibers which resulted in improvement of mechanical properties of composite. The TGA results showed that thermal stability of SCF/PP composites increased with increment of carbon fiber length. DMA results showed that storage and loss modulus of SCF/PP composites improved with incorporation of 5 and 10 mm length but for 1 and 2 mm length, no considerable change was observed. The Tg of composites with 5 and 10 mm length increased compare to unfilled PP. The performances of the composites were compared to the standard steel material applied and were found to be a viable replacement option. The composite showing the optimum properties within the investigation was one with 7% fiber content and 10 mm length.